PENGARUH PENYULUHAN KESIAPSIAGAAN BENCANA TERHADAP TINGKAT KESIAPSIAGAAN BENCANA GEMPA BUMI PADA SISWA SMP MUHAMMADIYAH SANDEN YOGYAKARTA - Wulandari, Endah Tri; Sujito, Rizky Ega (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2024)
Purpose: The purpose of this study is to determine the effect of disaster preparedness counseling on the level of earthquake disaster preparedness in students of SMP Muhammadiyah Sanden Yogyakarta. Methods: This type of research is a pre-experimental research with a one group pre-test-post-test design. The design of one group pretest-posttest involves one pre-selected group. In this design, testing is carried out twice, namely before the treatment called pre-test, and after the treatment called post-test. Results: Based on the results of bivariate analysis using the Wilcoxon Match Pairs Test based on p value (Asymp. Sig 2 tailed) of 0.000 which is less than the critical limit of the study of 0.05. So it can be concluded that there is an influence before and after disaster preparedness counseling on the level of earthquake disaster preparedness in students of SMP Muhammadiyah Sanden Yogyakarta Conclusion: Based on data analysis, it can be seen that there is an influence of disaster preparedness counseling on the level of earthquake disaster preparedness in students of SMP Muhammadiyah Sanden Yogyakarta.